2016
DOI: 10.1038/srep33924
|View full text |Cite
|
Sign up to set email alerts
|

Decreased IL7Rα and TdT expression underlie the skewed immunoglobulin repertoire of human B-cell precursors from fetal origin

Abstract: Newborns are unable to mount antibody responses towards certain antigens. This has been related to the restricted repertoire of immunoglobulin (Ig) genes of their B cells. The mechanisms underlying the restricted fetal Ig gene repertoire are currently unresolved. We here addressed this with detailed molecular and cellular analysis of human precursor-B cells from fetal liver, fetal bone marrow (BM), and pediatric BM. In the absence of selection processes, fetal B-cell progenitors more frequently used proximal V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 76 publications
3
37
0
Order By: Relevance
“…TdT expression early in life temporally coincides with IL-7-dependent B lymphopoiesis. For example, human fetal B cell precursors have reduced expression of both IL-7 receptor ␣ (IL-7R␣) and TdT (19). Furthermore, humans with IL-7R␣ mutations have reduced expression of TdT in their pro-B cells (19).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…TdT expression early in life temporally coincides with IL-7-dependent B lymphopoiesis. For example, human fetal B cell precursors have reduced expression of both IL-7 receptor ␣ (IL-7R␣) and TdT (19). Furthermore, humans with IL-7R␣ mutations have reduced expression of TdT in their pro-B cells (19).…”
Section: Resultsmentioning
confidence: 99%
“…For example, human fetal B cell precursors have reduced expression of both IL-7 receptor ␣ (IL-7R␣) and TdT (19). Furthermore, humans with IL-7R␣ mutations have reduced expression of TdT in their pro-B cells (19). We have previously shown that murine antibody responses to Pneumovax23 require IL-7 (3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations